2009
DOI: 10.1007/s00296-009-1231-x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis and HIV infection: case report and review of the literature

Abstract: Since the 1980s, a host of autoimmune phenomena and rheumatologic illnesses have been linked to infection with the human immunodeficiency virus (HIV). Given the broad effects of this virus on both the humoral and cell-mediated arms of the immune system, illnesses such as polymyositis and Reiter's syndrome appear to be more prevalent in HIV-infected individuals and occur in the absence of well-described predispositions. The activities of some rheumatologic illnesses exhibit an inverse relationship with the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Idiopathic inflammatory myositis is a group of diseases charac- echorovirus [8], group A beta hemolytic streptococcus [9], human immunodeficiency virus [10], etc. One study reported that epitopes derived from homologous sequences shared between human skeletal myosin and Streptococcus M5 protein can stimulate T cells from patients with active JDM and induce various cytokines [11].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic inflammatory myositis is a group of diseases charac- echorovirus [8], group A beta hemolytic streptococcus [9], human immunodeficiency virus [10], etc. One study reported that epitopes derived from homologous sequences shared between human skeletal myosin and Streptococcus M5 protein can stimulate T cells from patients with active JDM and induce various cytokines [11].…”
Section: Discussionmentioning
confidence: 99%
“…This report of coincident SS and HIV may shed light on the pathogenesis of SS, which is likely an autoimmune disease (Magro et al 2011). Interestingly, other presumed autoimmune disorders such as Guillian–Barre syndrome, polymyositis, and dermatomyositis may present early in HIV disease, and autoantibodies are frequently detected in HIV patients (Brannagan and Zhou 2003; Carroll and Holmes 2011; Rajadhyaksha et al 2012; Zandman-Goddard and Shoenfeld 2002), suggesting that these individuals, though relatively immunosuppressed, are not invulnerable to autoimmune diseases. This case should raise awareness of SS as an etiology for encephalopathy and white matter changes even in patients with comorbid HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatomyositis (DM) is a systemic autoimmune disease characterized by inflammation in multiple organs, most commonly in the skin and muscle (8). The cause of DM is still unclear, but several potential triggers, such as cancer (9)(10)(11)(12) and viral infection (13)(14)(15)(16), have been reported. Especially, regarding the relationship between the pathophysiology of DM and cancer, the treatment of cancer which is associated with DM sometimes leads to an improvement in the DM-related symptoms.…”
Section: Introductionmentioning
confidence: 99%